Educational Quasi-Market in Chile: The Discourse of Policy Makers - Almonacid, Claudio; Luzón, Antonio; Torres, Mónica (Education Policy Analysis Archives, 2008)
The Chilean educational system is characterized by the functioning of a cuasi (free) market, in which increasing degrees of administrative, financial and curricular decentralization take place within a context where two constitutional rights are in conflict: the right to (free) education and the freedom of teaching. This conflict arose from the design and implementation of said decentralization policy due to its negative effects in the processes of social inclusion of children and youngsters. In order to understand why those two constitutional rights are in conflict, it must be taken into account that such decentralization policy was designed by the military regime (1973-1990) as one of several neoliberal policies implemented in many different fields of the Chilean society, and that said policy has been kept in effect by the subsequent administrations of the “Concertación de Partidos por la Democracia” (Coalition of Parties for Democracy) (since 1990 to present) in a so called “transition process to democracy.” This research paper is intended to understand how the process of educational decentralization was conceived and how the system is in effect up to the present, as well as to understand the effects it has had on the process of social exclusion. To do that, the views of selected policy makers who have had active participation in this process are analyzed. First, there is a reference to the way the Chilean educational system works, and then the opinions of several educational policy makers about the processes of educational decentralization and social exclusion are analyzed.